#### Answer

$64$

#### Work Step by Step

Recall the following rule: $x^{-n}=\frac{1}{x^{n}}$. Thus, we obtain:
$(\frac{1}{4})^{-3}=(\frac{1^{-3}}{4^{-3}})=(\frac{4^{3}}{1^{3}})=\frac{64}{1}=64$

Published by
Cengage Learning

ISBN 10:
1285194055

ISBN 13:
978-1-28519-405-9

$64$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.